2022
DOI: 10.1029/2022je007184
|View full text |Cite
|
Sign up to set email alerts
|

Deviation of Mercury's Spin Axis From an Exact Cassini State Induced by Dissipation

Abstract: The spin axis of Mercury is in a Cassini state (Figure 1). The latter describes a configuration in which the planet's spin axis and orbit normal remain coplanar to and precess about the normal to the Laplace plane (Colombo, 1966;Peale, 1969Peale, , 2006. The precession is retrograde, and the latest estimate of its period is 325, 513 ± 10, 713 years (Baland et al., 2017). Figure 2 shows the orientation in space of the spin axis reported in several recent studies, expressed at the J2000 epoch as is the usual con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, if present, its size is not known. Several studies have attempted to place bounds on the inner core size, either by investigating its dynamical influence on the librations (Dumberry, 2011;Dumberry et al, 2013;Koning & Dumberry, 2013;Peale et al, 2002;Van Hoolst et al, 2012;Veasey & Dumberry, 2011;Yseboodt et al, 2013) and the mantle obliquity (Dumberry, 2021a;MacPherson & Dumberry, 2022;Peale et al, 2016), or by constructing interior models that are consistent with the observed amplitude of librations and mantle obliquity (Dumberry & Rivoldini, 2015;Genova et al, 2019;Hauck et al, 2013;Knibbe et al, 2021;Knibbe & Van Westrenen, 2015;Steinbrügge et al, 2021). While no general consensus has emerged from these, they all point to an inner core that cannot be too large.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, if present, its size is not known. Several studies have attempted to place bounds on the inner core size, either by investigating its dynamical influence on the librations (Dumberry, 2011;Dumberry et al, 2013;Koning & Dumberry, 2013;Peale et al, 2002;Van Hoolst et al, 2012;Veasey & Dumberry, 2011;Yseboodt et al, 2013) and the mantle obliquity (Dumberry, 2021a;MacPherson & Dumberry, 2022;Peale et al, 2016), or by constructing interior models that are consistent with the observed amplitude of librations and mantle obliquity (Dumberry & Rivoldini, 2015;Genova et al, 2019;Hauck et al, 2013;Knibbe et al, 2021;Knibbe & Van Westrenen, 2015;Steinbrügge et al, 2021). While no general consensus has emerged from these, they all point to an inner core that cannot be too large.…”
mentioning
confidence: 99%
“…We do not have direct observations of the orientation of the spin axis of the fluid core, nor that of the inner core if present. However, we expect that they should also be in a Cassini state, and their orientations should differ from that of the mantle (Dumberry, 2021a;MacPherson & Dumberry, 2022;Peale et al, 2014Peale et al, , 2016. Their misalignment angles depend on the elliptical shapes of the core-mantle boundary (CMB) and inner core boundary (ICB)-which in turn depend on the interior structure, including the size of the inner core and its density contrast with the fluid core.…”
mentioning
confidence: 99%
See 1 more Smart Citation